Proses Penerbitan Izin Sea Trial Kapal Sv. Sv. Bourbon Jindamanee Pada Ksop Khusus Batam Oeh PT. Gemalindo Shipping Batam - Helfina Hutagaol; Lilis Lilis; Fadiyah Hani Sabila (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
The purpose of writing this paper is to understand in depth about how the Process of Issuing Sea Trial Permit for SV. Bourbon Jindamanee at Specialized KSOP Batam by PT. Gemalindo Shipping Batam. In this paper, the methods used are field research and library research. The result of this paper is the Sea Trial Permit Issuance Process of SV. Bourbon Jindamanee by PT. Gemalindo Shipping Batam run effectively even though the Foreign Ship Agency Approval (PKKA) is approaching its expiration date.The implemented system facilitates the permit application with clear and structured steps. The process starts with a notification from the sip owner to the agent, followed by document preparation, after which the application is submitted trough the KSOP portal where the documents are inputted and verified by thr officers of the Kesyahbandaran and Port Aouthority Office (KSOP). To improve the Sea Trial Permit issuance process, it is recommeded that each relevant party ensure regular updatesof information and improved coordination to speed up the administrative process. In addition, conduct training for the internal team to help reduce errors in submission and implement a feedback system to collect input from each related party to improve the process in the future.